PERIIMPLANTITELE-DIAGNOSTIC SI TRATAMENT - Lazar Elena Luminita; Norina Consuela Forna (Romanian Dental Association for Education, 2016)
Peri-implantitis describes a non-specific inflammation caused or maintained at the level of host tissues. Certain authors define two different clinical entities: Peri-implantitis - an inflammatory reaction with the loss of bone support in the tissues that surround a functional implant. Peri-mucositis - a reversible inflammatory reaction localized only in the soft tissues. Peri-implantitis may have only a part or all its specific symptoms: bleeding upon touch, increased depth of the pocket , mobility, suppuration and pain.A bacterial infection is most frequently described in relation to the biofilm (defined as a community of microorganisms integrated in a glycocalyx attached to a solid surface). The solid, sometimes rough surface of an implant shows better adherence conditions of the biofilm. The inflammatory response of the host tissues to the adherent biofilm to the implant surfaces is the most important etiologic factor of peri-implantitis.The treatment aims at the determining factor of peri-implantitis, namely bacterial plaque. That is why the following therapeutic objectives are observed: removal or modification of the bacterial plaque from the peri-implant sulcus; decontamination and conditioning of the implants surface, correction and elimination of sites which cannot be properly hygienized, determination of an efficient control protocol for the bacterial plaque, re-osteointegration